Faktor Keterlambatan Pada Proyek Pembangunan Gedung Balai Nikah dan Manasik Haji Keccamatan Dumoga Utara di Kabupaten Bolaang Mongondow - Hadi Riswanto, Teguh; Sari, Sely Novita; Maulana, Rizal (Retii, 2023)
In planning a project, it is necessary to have an activity schedule that can be used as a guide by implementers in carrying out their activities in the field, this shows that scheduling is very influential in the implementation of a project. Good project scheduling can make a project run effectively and efficiently, but in reality it is not always the same as what was planned. In this case, it can be seen in the implementation of the construction of the Marriage Hall and Hajj Pilgrimage Building in Dumoga Utara District in Bolaang Mongondow Regency. In the construction process for the construction of the Balai Nikah and Manasik Haji Building, North Dumoga District in Bolaang Mongondow Regency, there were delays caused by several factors in the field, resulting in a delay of 25 days which was originally planned to be completed in 120 days but in the field the project was completed in 145 days. Because this happens, an analysis of project scheduling is carried out in order to find out what causes delays in the project. From the results of the analysis obtained, the cause of the delay is in the foundation work item. Factors that cause delays are unfavorable weather, lack of labor, and contractors.